KAREN’S DINER JAKARTA MARKETING: UNIQUE SERVICE EXPERIENCE BECAME AUTOPILOT MARKETING - Joseph Aldo Irawan,; Veronica Halim,; Emik Rahayu,; Izza Ulumuddin Ahmad Asshofi, (International Journal Of Accounting, Management, And Economics Research, 2023)
In Hospitality industry, courtesy became the most important part doing a service to the guest. Karen’s Diner brings a new concept of hospitality which is different than the usual service. Using type unfriendly waiter/waitress when doing a service, became a kind of attraction for the guest that make them want to try the sensation the rough service. From hospitality point of view, this kind of service wasn’t proper for the guest. Especially in Indonesia well known for warm hospitality. But many people upload their experience in social media make them proud have tried Karen’s Diner. This research uses the qualitative descriptive and used data collection techniques such as literature studies, documentation through social media Tik Tok and internet source. Many customer feels proud and happy for trying Karen’s Diner because of Karen’s Diner existences on social media. They makes many posting on social media and goes viral. After many customer curious and try their service, some of the customers feels unpleasant because the service and post their experience in social media. So many pro’s and con’s on social media makes Karen’s Diner more famous. The source of the research object was limited from the papers, only can find on online source. The authors suggests to makes more research about Karen’s Diner to make it more valid. There’s no previous research about Karen’s Diner especially in marketing.